Risk of TB disease in individuals with cancer - T. Diefenbach-Elstob; S. Tabrizi; P. Rivest; A. Benedetti; L. Azoulay; K. Schwartzman; C. Greenaway (IJTLD Open)
BACKGROUND: Cancer increases the risk of developing TB disease; however, there are limited data on the magnitude of risk by cancer type and timing after diagnosis of cancer in low TB incidence settings. METHODS: We conducted a nested case-control study of persons in Quebec between 1993 and 2017, including people with TB disease and matched controls. Conditional logistic regression was used to estimate adjusted odds ratios (aORs) of developing TB among people with cancer overall, by sub-type, and by time from cancer to TB diagnosis. RESULTS: There were 4,283 people with TB disease and 268,420 matched controls. The median age for people with TB disease and controls was respectively 46 years (IQR 30–67) and 36 years (24–47). Prior exposure to cancer was associated with TB disease (aOR 6.3, 95% CI 5.3–7.6). The risk of TB diagnosis was highest within 3 months of cancer diagnosis (aOR 26.6, 95% CI 19.6–36.2), with 60% of diagnoses of TB disease occurring within 6 months of cancer diagnosis. CONCLUSION: Risk of TB varies over time and by cancer type. Screening and treatment should be considered for potentially preventable TB (diagnosed more than 6 months post-cancer), particularly in those with respiratory, haematologic, and head and neck cancers.